Dynamics of change glioneyronal complex retinal photodamage, usingmathematical modeling methods - Ye. Yu. Varakuta; A. V. Potapov; A. A. Zhdankina; M. V. Svetlik; Ye. P. Mikhulya; S. V. Logvinov; A. V. Gerasimov (Бюллетень сибирской медицины, 2012)
Using electron microscopy and morphometric analysis studied the structural changes of neurons and radial glia of the retina of white mongrel male rats when exposed to light (6000 lux) in the dynamics after 1, 7, 14 and 30 days. The proposed mathematical model has allowed a high degree of probability to assess the state of a pool of cells of the retina at specific times throughout the experiment. The most striking structures of the retina are neurosensory cells, and neurons of theinner retinal layers are less sensitive to these influences.